2022
DOI: 10.3390/molecules27154990
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Cetraria s. str.—A Review of Its Botany, Phytochemistry, Traditional Uses and Pharmacology

Abstract: The genus Cetraria s. str. (Parmeliaceae family, Cetrarioid clade) consists of 15 species of mostly erect brown or greenish yellow fruticose or subfoliose thallus. These Cetraria species have a cosmopolitan distribution, being primarily located in the Northern Hemisphere, in North America and in the Eurasia area. Phytochemical analysis has demonstrated the presence of dibenzofuran derivatives (usnic acid), depsidones (fumarprotocetraric and protocetraric acids) and fatty acids (lichesterinic and protolichester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Two major compounds were identified in this study, assigned as fumaroprotocetraric acid (Compound 10) and cetraric acid (Compound 14), found in C. islandica [48]. On the other hand, usnic acid (Compound 17) is the only compound belonging to dibenzofurans that was identified in this study and found in C. islandica [48,49].…”
Section: Discussionmentioning
confidence: 54%
“…Two major compounds were identified in this study, assigned as fumaroprotocetraric acid (Compound 10) and cetraric acid (Compound 14), found in C. islandica [48]. On the other hand, usnic acid (Compound 17) is the only compound belonging to dibenzofurans that was identified in this study and found in C. islandica [48,49].…”
Section: Discussionmentioning
confidence: 54%
“…As for the DPPH analysis, the three extracts evidenced an IC 50 value much higher than the gallic acid standard, suggesting a medium-low inhibition capacity of the study concentrations used; however, the extract of O. frigida continued to show better antioxidant These results correlate positively with the reports of extracts and compounds isolated from other lichen species that show highly effective phenolic concentration and antioxidant activity through Frontiers in Pharmacology frontiersin.org colorimetric techniques (Luo et al, 2009;Mitrović et al, 2011;Jha et al, 2017;Studzińska-Sroka et al, 2021a;Elečko et al, 2022) and electrochemical, computational, and genetic studies (Kalra et al, 2023;Yañez et al, 2023). Likewise, the variability in the antioxidant properties of lichens is mediated by the geographical, altitudinal, and/or microhabitat conditions in which they develop working concentrations, metabolite isolation efficiency, types of solvent, and forms of extraction and exploration of the mechanisms of action (Ranković et al, 2012;White et al, 2014;Studzińska-Sroka et al, 2021b;Li et al, 2022;Popovici et al, 2022;Sánchez et al, 2022). On the other hand, the evident antioxidant capacity of lichenic species has supported their use for the evaluation of neuroprotective effects in in vitro and in vivo models, yielding positive results regarding cell viability, protection against induced oxidative stress, decrease in reactive oxygen species, improvement of mitochondrial function, and suppression of signaling pathways that induce inflammatory response in astrocytes (Fernández-Moriano et al, 2015;Fernández-Moriano et al, 2016;Lee et al, 2021;Ureña-Vacas et al, 2022b).…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 99%
“…Cetraria islandica Ach. represents the most investigated species from the pharmacological perspective among the 20,000 lichen species described worldwide [ 11 ].…”
Section: Introductionmentioning
confidence: 99%